Synthetic and biological aspects of studying the properties of 1, 2, 4-triazole derivatives - Khilkovets, A. V.; Karpenko, Yu. V.; Bigdan, O. A.; Parchenko, M. V.; Parchenko, V. V.; Хільковець, Анастасія Валеріївна; Карпенко, Юрій Вікторович; Бігдан, Олексій Антонович; Парченко, Марина Вікторівна; Парченко, Володимир Володимирович (My University, 2022)
The aim of our work was to analyze and summarize the known literature data on new synthetic approaches to the production of new derivatives of 1,2,4-triazole and systematize information related to the biological properties of these compounds.
Keywords: 1,2,4-triazole; medical chemistry; biological activity; heterocycle; organic chemistry